2014
DOI: 10.1177/1359105314555169
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nature relatedness and anxiety

Abstract: This study investigated the relationship between anxiety and feelings of being connected to nature. Two standardised self-report scales, the Nature Relatedness Scale (NRS) and the State Trait Inventory for Cognitive and Somatic Anxiety (STICSA) were used in tandem with a qualitative question. Quantitative results indicated that connection to nature was significantly related to lower levels of overall, state cognitive and trait cognitive anxiety.Qualitative results revealed seven themes; relaxation, time out, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(147 citation statements)
references
References 32 publications
6
137
2
2
Order By: Relevance
“…Interestingly, people who spent relatively more time out of doors had higher nature relatedness, suggesting that the recent doses of nature may contribute towards shaping nature orientation. Maintaining nature around the home may therefore be critical for both health and biological conservation, because nature orientation has been associated with improved life happiness [46,47], reduced anxiety [45] and environmental behaviour [67]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, people who spent relatively more time out of doors had higher nature relatedness, suggesting that the recent doses of nature may contribute towards shaping nature orientation. Maintaining nature around the home may therefore be critical for both health and biological conservation, because nature orientation has been associated with improved life happiness [46,47], reduced anxiety [45] and environmental behaviour [67]. …”
Section: Discussionmentioning
confidence: 99%
“…Engagement with the natural world increases feelings of connection, unity or being part of the natural world, which has been linked to psychological health [44]. Indeed, increased nature connection has been associated with improved mental health [45] and subjective well-being [46,47]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies that have examined the relationship between anxiety and green exercise have focused on the benefits of short bouts of green exercise on state anxiety and found that the greenness of the environment while exercising was more likely to be related to reductions in state anxiety than exercise on its own (Mackay and Neill, 2010). Regular exercise has also been associated with lower trait anxiety (Paluska and Schwenk, 2000) and as a result researchers have proposed that participation in regular green exercise is likely to be related to low levels of trait anxiety (Pretty et al, 2007; Martyn and Brymer, 2016). Studies have also found that nature can help manage and reduce the effects of stress, which if chronic might lead to anxiety (Vyas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the measurable psychological construct of nature relatedness (see also nature connectivity, nature connectedness) captures to what extent an individual has an awareness of, and fascination with, the natural world; nature relatedness also assesses the degree to which an individual has an interest in making contact with nature. Since nature relatedness has been linked with health and wellbeing, it is considered a psychological asset [134,135]. However, it may also be a planetary health asset because emerging research shows that nature relatedness is positively associated with empathy, pro-environmental attitudes and humanitarianism (and negatively with materialism) [136][137][138].…”
Section: Moving Upstream-the Psyche Of Planetary Healthmentioning
confidence: 99%